An investigation of microstructural, magnetic and microwave absorption properties of multi-walled carbon nanotubes/Ni0.5Zn0.5Fe2O4 - Muhammad Syazwan, Mustaffa; Raba’ah Syahidah, Azis; Nor Hapishah, Abdullah; Ismayadi, Ismail; Idza Riati, Ibrahim (Nature, 2019)
The enhancement of microwave absorbing properties in nickel zinc ferrite (Ni0.5Zn0.5Fe2O4) via multiwall carbon nanotubes (MWCNT) growth is studied in this research work. Ni0.5Zn0.5Fe2O4 was initially synthesized by mechanical alloying followed by sintering at 1200 °C and the microstructural, electromagnetic and microwave characteristics have been scrutinized thoroughly. The sintered powder was then used as a catalyst to grow MWCNT derived from chemical vapor deposition (CVD) method. The sample was mixed with epoxy resin and a hardener for preparation of composites. The composite of multi-walled carbon nanotubes/Ni0.5Zn0.5Fe2O4 shown a maximum reflection loss (RL) of −19.34 dB at the frequency and bandwidth of 8.46 GHz and 1.24 GHz for an absorber thickness of 3 mm for losses less than −10 dB. This acquired result indicates that multi-walled carbon nanotubes/Ni0.5Zn0.5Fe2O4 could be used as a microwave absorber application in X-band.